Urban dynamics suburbanisation and the mechanism of Urban Sprawl - Tanaka, Arthur; Dannaher,Brendan; Shephard, Phil; Classroom Video Pty. Ltd. (Bendigo, Vic. : Classroom Video, 2005)
This program offers a concise overview of today's city living. It explains the impact of city life on productivity and the economy as well as the concepts of'Time-Travel Budget Constancy' and'Urban Sprawl'
Executive producer, John Davis ; sound, Phil Maquire ; camera, Peter Been
Keywords: Urbanization; Suburbs; Suburban life